Distribution of blaTEM, blaSHV, blaCTX-M, blaOXA, and blaDHA in Proteus mirabilis Isolated from Diabetic Foot Infections in Erbil, Iraq - Fattah Hamid, Samira; Bahadeen Taha, Aza; Jamel Abdulwahid, Muhsin (Cellular and Molecular Biology, 2020)
Diabetic foot infection is considered to be one of the most important medical, economic, and social problems and a major cause of morbidity and mortality. Proteus mirabilis is a common etiologic agent of diabetic foot infections. This study aimed to determine the prevalence of beta-lactamase genes in P. mirabilis recovered from patients with diabetic foot wounds in Erbil, Iraq. Eighteen P. mirabilis isolated from 84 patients with diabetic foot ulcers were first phenotypically examined for the existence of extended-spectrum beta-lactamases by combined disc method and double-disc synergy method that all isolates showed positive results by both methods. The results were confirmed genetically by PCR to detect beta-lactamase-encoding genes (blaTEM, blaSHV, blaCTX-M, blaOXA, and blaDHA). The results revealed that all isolates contained extended-spectrum beta-lactamase and that 80% of the P. mirabilis isolates contained blaDHA, 60% had blaTEM, 53.3% had blaOXA, and 26.7% had blaCTX-M, whereas no isolates harbored blaSHV. The coexistence of two or more beta-lactamase genes in one isolate was observed. The existence of four genes (blaTEM + blaCTX-M + blaOXA + blaDHA) in the same isolate was documented in two isolates. In conclusion, this is the first study that reports a high prevalence of blaDHA and the coexistence of four resistance genes in the same organism in P. mirabilis isolated from diabetic foot patients in Iraq.